Reduced LPL and subcutaneous lipid storage capacity are associated with metabolic syndrome in postmenopausal women with obesity - M. C. Serra; A. S. Ryan; A. P. Goldberg (Wiley, 2017)
Sumary Objectives This study examines the hypothesis that lower adipose tissue lipoprotein lipase (LPL) activity and a limited capacity for subcutaneous adipocyte expansion will be associated with metabolic syndrome (MSyn) in postmenopausal women who are overweight and obese. Methods Women (N = 150; age 60 ± 1 year; BMI: 31.5 ± 0.3 kg m−2; mean ± standard errors of the means [SEM]) with and without MSyn had dual‐energy X‐ray absorptiometry scans for total body fat, CT scans for visceral and subcutaneous abdominal adipose tissue areas, lipid and glucose metabolic profiles, and abdominal and gluteal fat aspirations for subcutaneous fat cell weight (FCW; N = 150) and LPL activity (N = 100). Results Women with MSyn had similar total body fat, but 15% larger abdominal and 11% larger gluteal FCWs and more visceral fat (179 ± 7 vs. 134 ± 6 cm2) than women without MSyn (P's < 0.05). Abdominal LPL activity was 13% (P = 0.18) lower in women with than without MSyn and correlated with abdominal FCW (r = 0.49, P < 0.01) only in those without MSyn. Visceral fat and abdominal and gluteal FCWs correlated with MSyn components, and subcutaneous adipose tissue correlated with abdominal FCW (r = 0.43, P < 0.01) and LPL activity (r = 0.18, P < 0.05), independent of total body fat. Conclusions These results show that women with MSyn have lower LPL activity, limited capacity for subcutaneous adipocyte lipid storage and greater ectopic fat accumulation in viscera than women without MSyn of comparable obesity. This suggests that the development of novel therapies that would enhance adipocyte expandability might prevent the accumulation of ectopic fat and reduce the risk for MSyn in postmenopausal women with obesity.